In Vivo and Ex Vivo Evaluation of Inflammation and Apoptosis Induced after SMILE Procedures for Different Refractive Error Range. (4th May 2017) - Mastropasqua, Leonardo; Calienno, Roberta; Curcio, Claudia; Mastropasqua, Rodolfo; Nubile, Mario; Salgari, Niccolò; Lanzini, Manuela
ABSTRACT: Purpose : To detect corneal inflammation and apoptosis induced after small incision lenticule extraction (SMILE) at different refractive corrections for moderate to high values of myopia. Methods : Fifty patients (50 eyes) suffering from medium to high myopia (spherical equivalent refraction from −3.75 to −10.00 diopters (D) with refractive astigmatism under −0.75 D) underwent SMILE in order to correct myopic error. In vivo evaluation was done by corneal confocal microscopy (IVCM) and ex vivo by immunohistochemistry. After surgery, all corneal lenticules were checked for regularity, entirety, and fixed in formalin for immunohistochemistry evaluation of apoptosis (TUNEL) and inflammation (CD11b) levels. Postoperative assessments took place during the first week and the first and third months after surgery. Patients returned for IVCM examination for analysis of the corneal stromal femtosecond laser treatment interfaces reflectivity. Results : No correlation was observed between treated myopic refractive error and number of CD11b + and TUNEL + cell in all analyzed extracted lenticules. IVCM at 1 week and 1 month of follow-up showed numerous reflective particles at the laser treatment interface with a moderate light scattering. In semi-quantitative analysis of reflectivity intensity at the laser interfaces, a statistical difference was evident only between 1 week and 1 month ( p = 0.0213). Conclusions : SMILE, as an innovative all-femto surgical procedure, results in a reduced tissue inflammation and apoptosis levels with a minimum tissue response, in terms of interface reflectivity, and there are no statistically significant differences among variable treated refractive error range.